2007
DOI: 10.1039/b700161d
|View full text |Cite
|
Sign up to set email alerts
|

New insight into selective catalytic reduction of nitrogen oxides by ammonia over H-form zeolites: a theoretical study

Abstract: Density functional theory calculations were carried out to investigate the reaction mechanism of selective catalytic reduction of nitrogen oxides by ammonia in the presence of oxygen at the Brønsted acid sites of H-form zeolites. The Brønsted acid site of H-form zeolites was modeled by an aluminosilicate cluster containing five tetrahedral (Al, Si) atoms. A low-activation-energy pathway for the catalytic reduction of NO was proposed. It consists of two successive stages: first NH(2)NO is formed in gas phase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
79
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(91 citation statements)
references
References 44 publications
11
79
1
Order By: Relevance
“…44,45 Currently, a clear mechanism for NO oxidation to NO 2 on the Cu ion is under debate and have not been achieved yet. Some previous studies stated that NO was oxidised by O 2 in the gas phase or in pores of zeolites (O 2 + 2NO −−→ 2 NO 2 ), 18 but it is a three-molecule reaction thus its contribution to the overall NO oxidation is limited. We suggest that the elementary reaction here is…”
Section: No and Cu + Oxidation By Omentioning
confidence: 99%
See 4 more Smart Citations
“…44,45 Currently, a clear mechanism for NO oxidation to NO 2 on the Cu ion is under debate and have not been achieved yet. Some previous studies stated that NO was oxidised by O 2 in the gas phase or in pores of zeolites (O 2 + 2NO −−→ 2 NO 2 ), 18 but it is a three-molecule reaction thus its contribution to the overall NO oxidation is limited. We suggest that the elementary reaction here is…”
Section: No and Cu + Oxidation By Omentioning
confidence: 99%
“…Many previous studies showed it a relatively easily process in the B-site of zeolites by a hydrogen push-pull mechanism. 18,21 We here investigated its decomposition on both Brønsted acid and Lewis acid site, finding that the Brønsted site is indeed more favourable, and all intermediates and transition states were identified (Fig. S5).…”
Section: Nh 2 No Decomposition Into H 2 O and Nmentioning
confidence: 99%
See 3 more Smart Citations